(untitled) (Revista Inclusiones, 2021)
Satisfaction is a problem that is constantly provoking the attention of theory and practice in tourism industry. And if for the mass forms of tourism satisfaction is partially dependent on price, then regarding the luxury tourism its performance is the result of the proceeding of specific and often irrational effects. Building on such an unconventional starting point, the present study aims to deploy theoretically and to propose an explanation of luxury tourism behaviour by exploring well-established consumer models. The purpose is to trace the boundary markers of satisfaction for "luxury" tourists in order to identify the possibilities for their inclusion in a particular model. Luxury is a sign of social stratification, in which the understanding of the driving mechanisms determines the ability to establish its underlying principles. By analysing and understanding the essence and mechanisms of luxury, it is seeming that the idea and aspirations for lux are deeply rooted in human nature. The research is determined by the perception that luxury is an integral part of humanity and way of life in human societies and explores the link between behavioural intention and consumer satisfaction.